2003
DOI: 10.1002/glia.10222
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed proteins in human glioblastoma cell lines and tumors

Abstract: KEY WORDSproteomics; matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF); liquid chromatography tandem mass spectrometry (LC-MS-MS); glioblastoma; U87MG; major vault protein; cystatin B; Hsp27; tissue transglutaminase; epidermal growth factor receptor ABSTRACT An in-frame deletion of 801 bp in exons 2-7 (type III mutation) of the epidermal growth factor receptor (EGFR) is detected at high incidence in primary glioblastoma tumors. A proteomic approach was used to generate differential protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
96
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 44 publications
11
96
0
Order By: Relevance
“…The data revealed distinct differences between radiotherapy-treated and untreated glial tumours in an experimental glioma animal model. Significant differences were also detected between glioma and normal brain, which is consistent with previous studies on both glioma (Zhang et al, 2003;Iwadate et al, 2004) and other types of tumours (Melle et al, 2004). It is obvious that our method permits tumour progression to be monitored over time, since protein profiles from different time points during tumour growth formed subgroups in score space when modelled with PCA.…”
Section: Discussionsupporting
confidence: 88%
“…The data revealed distinct differences between radiotherapy-treated and untreated glial tumours in an experimental glioma animal model. Significant differences were also detected between glioma and normal brain, which is consistent with previous studies on both glioma (Zhang et al, 2003;Iwadate et al, 2004) and other types of tumours (Melle et al, 2004). It is obvious that our method permits tumour progression to be monitored over time, since protein profiles from different time points during tumour growth formed subgroups in score space when modelled with PCA.…”
Section: Discussionsupporting
confidence: 88%
“…Drug resistance is a complex process that involves hundreds of changes in gene expressions. To date, many types of proteins have been identified that are altered in drug-resistant cells, such as membrane proteins (35), proteins associated with glutathione transferases and detoxification (28), and proteins of the DNA repair system (36). From the perspective of transcriptional regulation, it has been shown that chemotherapy activates NF-nB, which results in resistance to apoptosis (37).…”
Section: Discussionmentioning
confidence: 99%
“…This EGFRvIII mutation confers enhanced tumorgenicity in vivo, 61 and there is differential expression of the EGFR protein compared to the U87MG parental cell line. 62 Cells were harvested by trypsinization in EDTA/trypsin, washed in PBS, and centrifuged three times at 200 g for 2 min. Cell number was determined and mice were anesthetized with isofluorane anesthesia and the scalp was swabbed with alcohol.…”
Section: Methodsmentioning
confidence: 99%